(untitled) (Journal of actual problems of jurisprudence, 2019)
The article discusses the impact of harm on the environment from the effects of cars, also brings the arguments of the parties technical harm to the environment, as well as questions about the reduction of traffic rules in compliance with international standards and increase the number of electronic cameras, increased requirements of the law against offenders and uvilichenie size fines in order to increase the responsibility of drivers. Revealed question about, traffic violations, measures to curb them by increasing penalties and sanutsy of Applications by electronic cameras, any requirements for the participation of the human factor in the city. Key words: atmosphere, machine, environmental issues, environmental damage, Euro standard.